Why Do Actions in Slow Motion Appear to Last Longer? On the Effect of Video Speed Information. (January 2021) - Sperl, Laura; Hüttner, Norman; Schroeger, Anna
When displayed in slow motion, actions are often perceived longer compared with original speed. However, it remains to be determined why this bias exists. Is it possible that the bias emerges because participants underestimate the factor by which a video was slowed down and hence arrive at erroneous conclusions about the original duration? If true, providing explicit information about the respective video speed should eliminate this slow motion effect. To scrutinize the nature of this bias, participants rated the original duration of sports actions displayed at original speed or slow motion. Results revealed the expected overestimation bias consisting in longer ratings with increasing slow motion. However, the bias disappeared when information about the current video speed was provided. The observations suggest an influence of knowledge about video playback speed on cognitive-evaluative processes which may hold important implications for future research and practice.